URGENSI PERENCANAAN PERKAWINAN DALAM MEMBENTUK KELUARGA SAKINAH PERSPEKTIF ISLAM - Nada Yoffa Primawita; Zakyyatus Nufus; Dita Safira; Siti Kholidah; Hunainah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Marriage in Islam is not only viewed as a physical and spiritual bond between a man and a woman, but also as a means of achieving a sakinah, mawaddah, and rahmah family. However, various household problems leading to conflicts and divorce indicate that many couples are not adequately prepared before entering married life. This study aims to examine the urgency of marriage planning in forming a sakinah family from an Islamic perspective. The study employed a qualitative method using a library research approach by analyzing the Qur'an, Hadith, books, and relevant scientific journals. The findings reveal that marriage planning plays a significant role in preparing individuals spiritually, psychologically, socially, and economically before marriage. From an Islamic perspective, such preparedness serves as the primary foundation for building harmonious relationships, fulfilling the rights and obligations of spouses, and dealing with various dynamics of family life. Proper marriage planning increases the likelihood of establishing a sakinah family because couples possess a better understanding of the purpose of marriage and the responsibilities that must be fulfilled. Therefore, marriage planning should become a primary concern for prospective couples as a preventive effort to create a high-quality and resilient family in accordance with Islamic values.